Bank Profitability Analysis: the Role of Liquidity, Company Size, Asset Quality and Leverage - Hartono, Ulil; Nurvitasari, Desi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 17 Nomor 2 Tahun 2023, 2023)
Banks are one of the most important sectors for a country’s economic growth, so banks must be appropriately managed. The success of bank management is reflected in resulting profitability. This research aims to analyse the effect of liquidity, firm size, asset quality, and leverage on bank profitability in 2017-2021. The population in this study is 27, and the sample is 25, which was selected using purposive sampling. This study uses secondary data from Bank financial reports obtained from the bank website. The result shows that liquidity and company size did not affect profitability, while asset quality and leverage affected profitability. This research implies that manager banks must pay attention to asset quality and leverage by considering the 5C principle in assessing creditworthiness. Keyword: Asset Quality; Company Size: Leverage; Liquidity; Profitability